2002
DOI: 10.1111/j.1151-2916.2002.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivities of (CeO2)1−x(Y2O3)x Thin Films

Abstract: Electrical properties of CeO2 thin films of different Y2O3 dopant concentration as prepared earlier were studied using impedance spectroscopy. The ionic conductivities of the films were found to be dominated by grain boundaries of high conductivity as compared with that of the bulk ceramic of the same dopant concentration sintered at 1500°C. The film grain‐boundary conductivities were investigated with regard to grain size, grain‐boundary impurity segregation, space charge at grain boundaries, and grain‐bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…For sample A, only one arc can be observed in the range of measured frequencies. We think that the grain arc has a small time constant and will happen at higher frequency beyond the limit of our instrument, so that the measured arc can be considered as the contribution of grain boundaries [14]. Two semicircles at high and low frequencies correspond to the time constants of the bulk grain and grain boundary, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sample A, only one arc can be observed in the range of measured frequencies. We think that the grain arc has a small time constant and will happen at higher frequency beyond the limit of our instrument, so that the measured arc can be considered as the contribution of grain boundaries [14]. Two semicircles at high and low frequencies correspond to the time constants of the bulk grain and grain boundary, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Activation energies for conduction are calculated by fitting experimental data to Eq. (2), [14] A 0 exp…”
Section: Resultsmentioning
confidence: 99%
“…high ionic conductivity (-0.63 s/cm at 700 8C), low activation energy (70 kJ/mol) and very small grain boundary resistance) through the examination of sintering behavior and ionic conductivity of Y x Ce 12x O 22d ðx ¼ 0:1 -0:33Þ specimens. Tian and Chan [11] investigated the conducting property in Y doped CeO 2 thin film. They concluded that space charge layer around grain boundary strongly affected conductivity.…”
mentioning
confidence: 99%
“…It was considered that stress between the interface of Y 2 O 3 and ZnS was released by SiO2 buffer layer. In fact, SiO2 film has already been used as buffer layer by Spankova et al and Tian et al in bY 2 O 3 /aSiO 2 /Si system [9,21]. Fig.…”
Section: Methodsmentioning
confidence: 95%